2016
DOI: 10.1016/j.amjmed.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Restricting Symptoms Before and After Admission to Hospice

Abstract: Background Prior work has shown that symptoms leading to restrictions in daily activities are common at the end of life. Hospice is a Medicare benefit designed to alleviate distressing symptoms in the last 6 months of life. The effect of hospice on the burden of such symptoms is uncertain. Methods From an ongoing cohort study of 754 community-dwelling older persons, aged 70 years or older, we evaluated 241 participants who were admitted to hospice from March 1998 to December 2013. A set of 15 physical and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…End‐of‐life for patients dying from gastrointestinal malignancies has been characterized by a high symptom burden and increased health care utilization . Merchant et al evaluated the symptom profile the year before death of patients dying from esophageal, gastric, colon and anorectal cancers and noted that the last months of life were characterized by moderate‐severe fatigue, as well as lack of well‐being and appetite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…End‐of‐life for patients dying from gastrointestinal malignancies has been characterized by a high symptom burden and increased health care utilization . Merchant et al evaluated the symptom profile the year before death of patients dying from esophageal, gastric, colon and anorectal cancers and noted that the last months of life were characterized by moderate‐severe fatigue, as well as lack of well‐being and appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these high costs, quality‐of‐life has been reported to be suboptimal. Specifically, the life of individuals who are seriously ill and dying is plagued with a high symptom burden characterized by pain, fatigue, anxiety, depression, and nausea . Hospice aims to provide compassionate care to individuals facing a life‐limiting illness, such as pancreatic cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier article, we reported that the number of restricting symptoms decreased significantly after the start of hospice, a well‐established source of palliative care at the end of life, with large reductions in the occurrence of restricting fatigue, depression, anxiety, and arm and leg weakness. Although hospice care is readily available for older persons at the end of life, its short duration diminishes its benefits .…”
Section: Discussionmentioning
confidence: 99%
“…washing, dressing, moving, eating meals and controlling urine and stool excretion causing dependence on other people, reduces the subjective assessment of the quality of life of hospice patients [37]. Most people admitted to the hospice indicate severe and moderate dependence in terms of simple and complex activities of everyday life and limited mobility [38].…”
Section: Variablesmentioning
confidence: 99%